The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3390/app11156714
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Dietary Supplementation of Flaxseed Meal on Intestinal Morphology, Specific Enzymatic Activity, and Cecal Microbiome in Broiler Chickens

Abstract: The use of natural feed additives could be a beneficial approach to maintaining the health of chickens and a way to improve food digestion. Flaxseed is a rich source of omega-3 fatty acid, alpha linolenic acid, oleic acid, and fiber. The purpose of this study was to evaluate the effects of dietary inclusion of 4% flaxseed on the intestinal morphology, specific enzymatic activity, and cecal microbiome in broiler chickens. The 4-week feeding trial was conducted on 100 Cobb 500 (14 days of age) unsexed broiler ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 67 publications
0
5
0
Order By: Relevance
“…Although the composition of intestinal microbes at different developmental stages is tightly regulated, the developmental time and succession of intestinal microbes are affected by various factors ( Pandit et al ., 2018 ; Ngunjiri et al ., 2019 ). Studies have confirmed the influence of production management, diet, disease, genetics, and other factors on the composition of gut microbes ( Yadav and Jha, 2019 ; Popescu et al , 2021 ; Upadhaya et al , 2021 ; Jia et al , 2022 ; Liu et al , 2022a ). Importantly, there is an urgent demand for green antibiotic substitutes in the chicken industry following widespread concerns regarding antimicrobial resistance and consequent antibiotic bans.…”
Section: Butyricum Interacts With Gut Microbes Toregulate Intestinal ...mentioning
confidence: 90%
See 1 more Smart Citation
“…Although the composition of intestinal microbes at different developmental stages is tightly regulated, the developmental time and succession of intestinal microbes are affected by various factors ( Pandit et al ., 2018 ; Ngunjiri et al ., 2019 ). Studies have confirmed the influence of production management, diet, disease, genetics, and other factors on the composition of gut microbes ( Yadav and Jha, 2019 ; Popescu et al , 2021 ; Upadhaya et al , 2021 ; Jia et al , 2022 ; Liu et al , 2022a ). Importantly, there is an urgent demand for green antibiotic substitutes in the chicken industry following widespread concerns regarding antimicrobial resistance and consequent antibiotic bans.…”
Section: Butyricum Interacts With Gut Microbes Toregulate Intestinal ...mentioning
confidence: 90%
“…, 2018 ). Therefore, dietary intervention is an important method for modifying gut microbes, regulating intestinal barrier function, and achieving significant improvements in chicken production performance ( Mikulski et al , 2020 ; Macit et al , 2021 ; Popescu et al , 2021 ; Moon et al , 2022 ; Obianwuna et al , 2022 ; Qiu et al , 2022 ). Accordingly, research and development of novel prebiotic and probiotic products are important for the chicken industry.…”
Section: Beneficial Properties and Applications Of Probiotics In Chic...mentioning
confidence: 99%
“…It is interesting to note that when flaxseed meal is added to the diet of brown-layer hens, the digestibility of crude protein decreases, while at the same time, there is a rise in the production of eggs and the performance of the hen (Popescu et al 2021). This was found in research conducted by Popescu et al (2021).…”
Section: Beneficial Effects Of Flaxseed On Layer Productionmentioning
confidence: 99%
“…The result of this research showed that the use of microwaved flaxseed flour as feed gave a highly significant effect (p<0.01) on increasing the amylase activity of the broiler (Table 3). Previous research reported that broiler fed with 4% flaxseed flour increase the alpha-amylase activity (Popescu et al 2021). The increase in amylase activity may be due to the presence of linoleic acid (source of omega-6) contained in the flaxseed that plays a role as an activator in the process of amylase secretion carried out by pancreatic acinar cells (Wooten & Wrenn, 1988).…”
Section: The Effect Of Treatments On Broiler Digestive Enzyme Activitymentioning
confidence: 99%
“…Leghari et al (2017) reported that the use of flaxseed flour in broiler feed as much as 0 -15% increased average body weight and decreased feed consumption. The use of flaxseed flour as feed is also reported can increase the digestive enzyme activity of broiler (Popescu et al 2021). The present study was carried out to evaluate the effect of the use of microwaved flaxseed flour as broiler feed on the growth performance and digestive enzyme activity.…”
Section: Introductionmentioning
confidence: 98%